Inadvertent excision of malignant soft tissue tumours. Issue 6 (3rd June 2019) - Grimer, Robert; Parry, Michael; James, Steven
Abstract : Inadvertent excision of lumps which turn out to be sarcomas is not uncommon. Imaging has a limited role in detecting microscopic residual disease but can show the extent of the previous surgical field. Standard treatment is wide re-excision, usually combined with radiotherapy. Residual tumour is found in an average of 50% of reported cases. The presence of residual disease is an adverse prognostic factor. All lumps bigger than a golf ball should have a diagnosis prior to excision. Cite this article: EFORT Open Rev 2019;4 DOI: 10.1302/2058-5241.4.180060